Study And Evaluation on The Reachable of Closing Multi-Purpose Vehicle (MPV) Trunk for Female Participants - Mazlan, Muhammad Zarul Fikri (Progress in Engineering Application and Technology, 2022)
Multi-purpose vehicle or MPV had been the common transportation for Malaysian people especially the one that has large number of family members but the tall opened tailgate or trunk gave the problem for the female user that limited by their height. The main objective of this study is to investigate and evaluate the reach for female participant to close MPV/SUV trunk’s door and the study involving any female participants and the less advanced MPV that does not have any automatic system button or kick sensors, in the trunk system. The method being used was through the google form for the survey and the CATIA V5 software on the analysis. The findings obtained from the study is that from the survey there are minority respondents that faced the stated problem, and on CATIA Analysis showed the score of manikin posture. From the study and evaluation, it can be summarized that the RULA score of the posture was quite dangerous for human body, especially the respondents hat faced the problem.